The work-health balance questionnaire: cultural adaptation and validation in Spanish - Novelo-Ramírez, Hiram René; Méndez Magaña, Ana Cecilia; Herrera-Godina, Melva Guadalupe; González-Estévez, Guillermo; Martínez-Melendres, Berenice; Huerta-Pérez, Alba; Gragnano, Andrea (Anales de Psicología / Annals of Psychology, 2022)
This study aimed to adapt the Work-Health Balance questionnaire (WHBq; (Gragnano, Miglioretti, Frings-Dresen, & de Boer, 2017) into Spanish and to provide evidence for its factorial structure, reliability, and validity. WHBq comprises 17 items with three scales: Work-Health Incompatibility (WHI), Health Climate (HC) and External Support (ES). It was applied to a sample of Mexican workers (n =316). Confirmatory factor analysis revealed that the three-factor model replicating the original structure provided good fit (CFI = 0.950; SRMR = 0.051; RMSEA = 0.069). The reliability of each factor and the whole questionnaire were satisfactory (α and ω higher than 0.70). The AVE was lower than 0.50 only for ES. Solutions to this problem are discussed. Concurrent and differential validity was examined with external criteria. The WHBq in its Spanish version shows good psychometric properties and theoretically consistent relationships with external variables. These findings provide support for its use as a valid and reliable tool in Mexico.